Transitory electrochemical masking for precision jet processing techniques - Mitchell-Smith, Jonathon; Speidel, Alistair; Clare, A.T. (Elsevier, 2018)
Electrochemical jet processing techniques provide an efficient method for large area surface structuring and micro-milling, where the metallurgy of the near-surface is assured and not adversely affected by thermal loading. Here, doped electrolytes are specifically developed for jet techniques to exploit the Gaussian energy distribution as found in energy beam processes. This allows up to 26% reduction in dissolution kerf and enhancements of the defined precision metric of up to 284% when compared to standard electrolytes. This is achieved through the filtering of low energy at discrete points within the energy distribution curve. Two fundamental mechanisms of current filtering and refresh rate are proposed and investigated in order to underpin the performance enhancements found using this methodology. This study aims to demonstrate that a step change in process fidelity and flexibility can be achieved through optimisation of the electrochemistry specific to jet processes.